Selective Extraction and Bulk Liquid Membrane Transport of Cu(II) from Aqueous Nitrate Solution in the Presence of Zn(II), Ni(II) and Mn(II) Cations Using Benzoyl Acetone - A. Nezhadali; H. Vahedi; M. Roigar; A. Sadeghi (E-Journal of Chemistry)
The competitive metal ion extraction and transport of Cu(II), Ni(II), Zn(II) and Mn(II) with benzoyl acetone and EDTA was studied. In the experiments the ligand was dissolved in chloroform and the pH and time of extraction or transport were varied. Also the rate of shaking and ligand concentration on the efficiency of extraction and transport was studied. The results revealed that the ligands exclusively extract Cu(II) from the mixture of the above cations.